New Possibilities in Cultural Consumption. The Effect of the Global Pandemic on Listening to Music - Váradi, Judit (Central European Journal of Educational Research, 2021)
In this study, we address the impact of COVID-19 on classical music concerts. New forms of cultural consumption and their convenience have raised the question as to whether concert halls will still be needed in the future, and whether the audience will take on the extra time and effort to be present in person at a musical artistic event. In an analysis of international surveys, we formed an accurate picture of music listening habits in the period before and during the pandemic. We also administered a survey, completed by 134 music teachers. Although the findings cannot be generalised to society as a whole, the respondents in the sample are well acquainted with the artistic setting and possess sufficient prior experience, so their opinion is relevant to the topic. Despite the convenience of the online space and the rich selection of art available, the interviewed music teachers will still prefer live music events, which offer them a more profound experience.